Traditional Chinese Pregnancy Restrictions, Health-Related Quality of Life and Perceived Stress among Pregnant Women in Macao, China - Ying Lau, RN, RM, IBCLC, PhD (Elsevier, 2012)
Purpose: The objectives of this study were to identify the prevalence and rationales of traditional Chinese pregnancy restrictions and to investigate the relationship between pregnancy restriction, health-related quality of life, and perceived stress level at a two-stage design. Methods: Stage I consisted of exploring the traditional Chinese pregnancy restrictions and their underlying beliefs based on extensive literature review followed by in-depth interviews with 30 pregnant women. Stage II investigated the relationship between pregnancy restrictions, health-related quality of life, and perceived stress among 1,151 women. Self-developed traditional Chinese pregnancy restrictions lists were measured on adherence towards the traditional Chinese pregnancy restriction. Perceived stress and health-related quality of life were measured by the Perceived Stress Scale and the Short Form-12 (SF-12) Health Survey, respectively. Results: The majority of the women adhered to traditional Chinese pregnancy restrictions in order to protect the unborn child from danger and to avoid the problems associated pregnancy and birth, such as miscarriage, stillbirth, death of the mother, and imperfections in the newborn. Pregnant women who adhered to behavioral restrictions were more likely to associate with poor physical component of health-related quality of life. However, there was no significant difference between pregnancy restrictions and Perceived Stress Scale scores. Conclusion: The findings provided cultural rationales of pregnancy restrictions within a Macao context that may assist health professionals to better understand women from different cultures. It is essential in the development of culturally appropriate healthcare to support women in making a healthy transition to motherhood.